The Misinterpretation of Ibn Taymiyyah’s Mardin Fatwa by the Modern Jihadist - Hidayah, Alfina; Maghribi, Hamdan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
This article discusses how the Modern Jihadists used Mardin Fatwa of Ibn Taymiyyah as the basis of their ideology and actions. So this research presents its novelty with an explanation of how modern radicalism develops, Ibn Taymiyya’s fatwas which are used as the theological foundations of the radicals, and how Jihadists read Ibn Taymiyyah’s Mardin Fatwa to legitimate their actions. This qualitative research used the primary sources of Ibn Taymiyyah’s works and secondary sources from his students and the Taymiyyan studies as well to enrich the argument of the researcher to result in the conclusion that several statements are quoted and used by the Jihadists to legitimate their radical actions; Anti-Mongol Fatwas I, II, and III, as well as Mardin fatwa with erroneous interpretations and not in accordance with the context behind the issuance of the fatwa. Like Mardin fatwa, for example how radicals read peace and war zones by correlating Islamic government with dar al-silm and conventional government that is not based on Islamic law with dar al-ḥarb then consequently it must be fought as the radicalist did against Egyptian President Anwar Sadat. This is where the importance of understanding Ibn Taymiyyah’s text holistically, intertextually not partially so that it will obtain an understanding that is in accordance with -at least approaching - the original substance of the author.